A Catalyst of Acculturation of Korean Pop Culture Towards Religious Attitude and Habits of BTS Army Indonesia: A Review of Communication Study - Nasution, Nadya Amalia; Noffiyanti, Noffiyanti; Rahmawati, Berlian (West Science Interdisciplinary Studies, 2024)
This research examines how Korean pop culture, especially through the music group BTS, functions as a catalyst in influencing the religious attitudes and habits of their fans (Army) in Indonesia. Using a communication science framework, this research explores the process of intercultural communication that occurs through social media, as well as how the messages conveyed by BTS are constructed, disseminated, and interpreted by their fans. The research method used is a qualitative approach, involving in-depth interviews and participatory observation of members of the Lampung Army. Media content analysis was also carried out to understand the influence of BTS content on fans' religious attitudes and habits. The research results show that the influence of BTS and Korean pop culture creates a complex dynamic between the adoption of new cultural elements and the maintenance of existing religious values. The findings of this research provide insight into the role of communication in cultural acculturation and its impact on non-secular aspects of fans' lives, also contributing to the understanding of how media and intercultural communication can influence religious identity and practice in the era of digital globalization. These findings are important for cross-cultural studies, the sociology of religion, and communication science, and provide practical guidance for researchers and practitioners in the fields of communication and culture.